2014
DOI: 10.1002/jeab.123
|View full text |Cite
|
Sign up to set email alerts
|

The effect of response rate on reward value in a self‐control task

Abstract: To understand how effort, defined by number of responses required to obtain a reward, affects reward value, five pigeons were exposed to a self-control task. They chose between two alternatives, 2 s of access to food after a delay of 10 s, and 6 s of access to food after an adjusting delay. The adjusting delay increased or decreased depending on the pigeons' choices. The delay at which the two alternatives were equally chosen defined the indifference point. To determine whether requiring responses during the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 26 publications
6
10
0
Order By: Relevance
“…Nevertheless, response rate decreased during the last bin, both in the HR and BL phases. A similar pattern was also reported in Fortes et al (). This pattern may be due to pigeons anticipating the end of the delay and checking the feeder, which would prevent them from pecking the key.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Nevertheless, response rate decreased during the last bin, both in the HR and BL phases. A similar pattern was also reported in Fortes et al (). This pattern may be due to pigeons anticipating the end of the delay and checking the feeder, which would prevent them from pecking the key.…”
Section: Resultssupporting
confidence: 91%
“…These data are similar to those Fortes et al () reported and they support the hypothesis that the effort imposed through the relatively high response rate devalued the SS alternative, which in turn increased the preference for the LL alternative, yielding a higher indifference point.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations